background image

5.8. MORE ADVANCED PROPERTIES OF FILTERS

83

Proof.

We will prove only the first, as the second is dual.

Let’s denote the right part of the equality to be proven as

R

. First we will

prove that

R

is a filter.

R

is nonempty because

S

is nonempty.

Let

A, B

R

. Then

A

=

X

0

u

Z

· · ·u

Z

X

k

,

B

=

Y

0

u

Z

· · ·u

Z

Y

l

where

X

i

, Y

j

S

S

.

So

A

u

Z

B

=

X

0

u

Z

· · · u

Z

X

k

u

Z

Y

0

u

Z

· · · u

Z

Y

l

R.

Let element

C

w

A

R

. Consequently (distributivity used)

C

=

C

t

Z

A

= (

C

t

Z

X

0

)

u

Z

· · · u

Z

(

C

t

Z

X

k

)

.

X

i

P

i

for some

P

i

S

;

C

t

Z

X

i

P

i

;

C

t

Z

X

i

S

S

; consequently

C

R

.

We have proved that that

R

is a filter base and an upper set. So

R

is a filter.

Let

A ∈

S

. Then

A ⊆

S

S

;

R

K

0

u

Z

· · · u

Z

K

n

K

i

∈ A

where

i

= 0

, . . . , n

for

n

N

=

A

.

Consequently

A w

R

.

Let now

B ∈

A

and

∀A ∈

S

:

A w B

. Then

∀A ∈

S

:

A ⊆ B

;

B ⊇

S

S

. Thus

B ⊇

T

for every finite set

T

S

S

. Consequently up

B 3

d

Z

T

. Thus

B ⊇

R

;

B v

R

.

Comparing we get

d

F

(

Z

)

S

=

R

.

Corollary

518

.

The following is an implications tuple:

1

. (

A

,

Z

) is a powerset filtrator.

2

. (

A

,

Z

) is a primary filtrator over a distributive lattice.

3

. up

d

A

S

=

K

0

u

Z

···u

Z

K

n

K

i

S

h

up

i

S

where

i

=0

,...,n

for

n

N

for

S

P

A

\ {∅}

.

Proof.

1

2

Obvious.

2

3

By the theorem.

Theorem

519

.

Let

Z

be a distributive lattice. Then:

1

.

F

0

u

F

(

Z

)

· · · u

F

(

Z

)

F

m

=

n

K

0

u

Z

···u

Z

K

m

K

i

∈F

i

where

i

=0

,...,m

o

for any

F

0

, . . . ,

F

m

F

(

Z

);

2

.

F

0

t

I

(

Z

)

· · · t

I

(

Z

)

F

m

=

n

K

0

t

Z

···t

Z

K

m

K

i

∈F

i

where

i

=0

,...,m

o

for any

F

0

, . . . ,

F

m

I

(

Z

).

Proof.

We will prove only the first as the second is dual.

Let’s denote the right part of the equality to be proven as

R

. First we will

prove that

R

is a filter. Obviously

R

is nonempty.

Let

A, B

R

. Then

A

=

X

0

u

Z

· · · u

Z

X

m

,

B

=

Y

0

u

Z

· · · u

Z

Y

m

where

X

i

, Y

i

∈ F

i

.

A

u

Z

B

= (

X

0

u

Z

Y

0

)

u

Z

· · · u

Z

(

X

m

u

Z

Y

m

)

,

consequently

A

u

Z

B

R

.

Let filter

C

w

A

R

C

=

A

t

Z

C

= (

X

0

t

Z

C

)

u

Z

· · · u

Z

(

X

m

t

Z

C

)

R.

So

R

is a filter.

Let

P

i

∈ F

i

. Then

P

i

R

because

P

i

= (

P

i

t

Z

P

0

)

u

Z

· · · u

Z

(

P

i

t

Z

P

m

). So

F

i

R

;

F

i

w

R

.

Let now

B ∈

A

and

i

∈ {

0

, . . . , m

}

:

F

i

w B

. Then

i

∈ {

0

, . . . , m

}

:

F

i

⊆ B

.

Let

L

i

∈ B

for every

L

i

∈ F

i

.

L

0

u

Z

· · · u

Z

L

m

∈ B

. So

B ⊇

R

;

B v

R

.

So

F

0

u

F

(

Z

)

· · · u

F

(

Z

)

F

m

=

R

.